2015
DOI: 10.4155/fso.15.67
|View full text |Cite
|
Sign up to set email alerts
|

New Synthesis and Biodistribution of the D-Amino Acid Oxidase-Magnetic Nanoparticle System

Abstract: Background:Application of nanoenzymes, based on D-amino acid oxidase (DAAO) conjugated to magnetic nanoparticles (NPs), as anticancer system requires improvement of the synthesis protocol and in vivo distribution evaluation.Results:A new and more efficient synthesis via EDC-NHS produced an Fe3O4NP-APTES-DAAO system with a specific activity of 7 U/mg NPs. IR spectroscopy showed that all Fe3O4 NP sites are saturated with APTES and all available NH2 sites with DAAO. The acute cytotoxicity of the new system does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Moreover, cobalt NPs are magnetic and this property allows to manipulate them in a chemical or biological system using an external magnet. Moreover, magnetic NPs can be easily conjugated to biologically important constituents such as DNA, peptides, antibodies 24 as well as enzymes 25 26 and sugars 27 28 to construct versatile bio-nano hybrids.…”
mentioning
confidence: 99%
“…Moreover, cobalt NPs are magnetic and this property allows to manipulate them in a chemical or biological system using an external magnet. Moreover, magnetic NPs can be easily conjugated to biologically important constituents such as DNA, peptides, antibodies 24 as well as enzymes 25 26 and sugars 27 28 to construct versatile bio-nano hybrids.…”
mentioning
confidence: 99%
“…Since the specic activity of the RgDAAO stock solution was 59 U mg À1 , we estimated up to 24 U per mg of NP-APTES. The NPs here synthesized showed a smaller diameter compared to the ones used by Cappellini et al 24 and this allowed a 7 fold increase of the DAAO/NP (w/w) ratio.…”
mentioning
confidence: 90%
“…That resulted in an increased cellular internalization of the enzyme, a prolonged enzymatic activity and storage stability, and the possibility of targeting to the cancer mass with the help of an external magnetic eld. However, while the APTES functionalization represents a good amino group donor, its activation via glutaraldehyde can affect the enzyme integrity 21 leading to a loss of DAAO activity.22,23 Cappellini et al 24 reported a higher yield for the NP-DAAO synthesis when conducted via EDC/NHS instead of with glutaraldehyde. Furthermore, also the NP diameter and aggregation inuence the amount of loaded enzyme.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the various applications described above, iron-based NPs raise concerns for the potential risk of exposure through ingestion, which can occurs both into the aquatic environment, this being the ultimate recipient of NPs that are intentionally or accidentally spilled into it, and when they are used as nanoingredients. In vitro (Gornati et al 2016;Coccini et al 2019) and in vivo experiments on mammals (Cappellini et al 2015;Feng et al 2018) have been performed to evaluate iron NP toxicity. Moreover, several iron NPs (i.e.…”
Section: Introductionmentioning
confidence: 99%